Rozwój partii ultraprawicowych na przykładzie partii CHEGA podczas wyborów parlamentarnych w Portugalii w 2024 roku - Pankiewicz, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The party system in Portugal, has represented a democratic state for 51 years. After the overthrow of the right-wing dictatorship in 1974, political pluralism took hold. This also meant the return of far-right parties seeking to regain at least some power. None of these parties achieved a result in parliamentary elections like the CHEGA party, founded in 2019. This article is intended to provide an overview of the political background for far-right parties in Portugal, the history of the party, its founding, the profile of its leader, and to analyse the result of the 2024 parliamentary elections.
Keywords: CHEGA; rasizm; wybory; ultraprawica; Zgromadzenie Narodowe; Portugalia; racism; elections; National Assembly; ultra-right